Analisis Yuridis Penerapan Pasal 56 Kitab Undang-Undang Hukum Acara Pidana Dalam Peradilan Pidana Ditinjau Dari Kepastian Hukum dan Keadilan Hukum - Rahman, Muhammad Faiz; Husna, Aqila; Mihrab, Nurrahmah Stephanie; Oktaviana, Malkah Melia; Dariyah H, Salsabila Poetri (Jurnal Ilmiah Dinamika Hukum, 2025)
Abstract Indonesia is a country based on law and not based on mere power. A rule of law has a commitment to uphold every human right (HAM) and guarantees that every citizen has equal status before the law. Law has the aim of achieving peace, justice and benefits for society, in order to achieve order and tranquility in order to realize the supremacy of law. To realize legal supremacy, law enforcers are needed. This research uses a type of normative legal research, which is carried out by looking at secondary data or library sources which include primary and secondary legal documents. Criminal justice mechanisms in Indonesia still involve neglect of the Procedural Code. Criminal Procedure Code (KUHAP), especially in article 56. This is caused by law enforcers who think that the state is only obliged to offer and provide legal advice to accompany the defendant. If sanctions are not regulated for refusing to provide legal advice to the defendant, this will result in losses for the defendant in the investigation process starting from the police level to the judicial process, in which case it can be said that there is a legal vacuum. Keywords: Article 56 KUHAP, Legal Certainty, Legal Justice